2006
DOI: 10.1111/j.1540-8159.2006.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of Pacing Threshold as Determined by an Automatic Ventricular Threshold Testing Algorithm

Abstract: In this case report, we describe markedly different pacing thresholds determined by a manual threshold test and the automatic Ventricular Capture Management algorithm. The discrepancy in pacing threshold values reported was due to the difference in the AV intervals used with the different testing methods. We propose that the differences in right ventricular dimensions with altered diastolic filling periods affected the threshold in this patient with a new passive fixation lead in the right ventricular apex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Automatic threshold measurement algorithms have been developed to: (1) manage the trade‐off between device longevity and safety; (2) decrease the time spent (patient and physician) managing device follow‐up in the clinic 1 and to detecting clinically actionable events 2 ; and (3) facilitate remote management of pacing devices. In order to accomplish these goals, the automatic threshold measurement algorithms must accurately measure the threshold of all leads and measure the threshold with enough frequency to adapt to any changes in threshold 3–10 …”
Section: Introductionmentioning
confidence: 99%
“…Automatic threshold measurement algorithms have been developed to: (1) manage the trade‐off between device longevity and safety; (2) decrease the time spent (patient and physician) managing device follow‐up in the clinic 1 and to detecting clinically actionable events 2 ; and (3) facilitate remote management of pacing devices. In order to accomplish these goals, the automatic threshold measurement algorithms must accurately measure the threshold of all leads and measure the threshold with enough frequency to adapt to any changes in threshold 3–10 …”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of AV interval‐dependent crosstalk is most probably related to the timing of atrial systole and its impact on changes in RV filling, volume, and dimensions. In this respect, the effect of critically timed atrial systole on the RV pacing threshold has been reported in single‐chamber ventricular pacemakers 1–5 . This phenomenon appears to be related to changes in RV volume and possibly lead movement.…”
Section: Discussionmentioning
confidence: 96%
“…This algorithm measures the stimulation threshold and automatically updates the pacing output to maximize the device's longevity. This algorithm is widely used and has proven to be useful and safe; however, there are occasional reports of pacing failure owing to erroneous measures [ 12 , 13 ]. The algorithm was considered inaccurate in one patient with AF and complete AV block.…”
Section: Discussionmentioning
confidence: 99%